Longitudinal Evaluation of Dravya and Guna Samanya Principles: A Drosophila melanogaster Model of Tissue Accretion Using Aja Mamsa (Capra hircus meat) and Masha (Vigna mungo). - Dr. Sumith Kumar M,; Dr. Jayaram Krishna M,; Dr. Rinjin G Krishna, (The Bioscan, 2026)
The Samanya Vishesha Siddhanta is a basic therapeutic principle of Ayurveda wherein similarity leads to accumulation of tissues and dissimilarity leads to depletion. The present study is an attempt to evaluate two traditional methods of treatment for tissue wasting (Dhatu Kshaya) in a longitudinal way using Dravya Samanya (substance homology) with AjaMamsa (goat meat) and Guna Samanya (quality homology) with Masha (black gram). The study used an in vivo model of Drosophila melanogaster (N=400 wild type flies). The flies were randomised into four groups: Full diet control (C1), Nutrient restricted half diet control (C2), Masha Vesavara Test group (T1) and AjaMamsa Vesavara Test group (T2). Test diets were formulated with 10% w/v of the respective extracts. Morphometric data (total body weight, axis length, abdominal width and Body Mass Index (BMI)) were collected over a 30-day period, and analysed by Two-Way Repeated Measures ANOVA and Tukey's HSD post-hoc test. The nutrient-restricted cohort (C2) exhibited a steady decline in body mass by 5.88% at Day 30. Both the AjaMamsa and Masha treatments reversed this wastage trend and resulted in significant gains in mass. However, the AjaMamsa cohort (T2) showed a significantly better gain of 24.75% mass gain as against the 19.00% gain in the Masha cohort (T1) (p<0.01) . The AjaMamsa group also showed large increases in abdominal width. The trends in BMI were similar for all the groups for the 30 days thus eliminating isolated and unhealthy deposition of lipids and confirming the proportional and healthy structural tissue (Mamsa Vardhana). The empirical data support the therapeutic superiority of Dravya Samanya (AjaMamsa) over Guna Samanya (Masha) in building and restoring the tissue mass. These findings provide support for an evidence-based clinical hierarchy for treatment of structural wasting, with direct homologous substances being the primary intervention.